Femtosecond laser induced low propagation loss waveguides in a lead-germanate glass for efficient lasing in near to mid-IR - Mamoona Khalid (Nature Portfolio, 2021)
Abstract To support the growing landscape of near to mid-IR laser applications we demonstrate a range of low propagation loss femtosecond laser (FSL) written waveguides (WGs) that have achieved guided-mode laser operation in a rare earth (RE) doped lead-germanate glass. The WGs are fabricated in both the athermal and thermal FSL writing regimes using three different pulse repetition frequencies (PRF): 100 kHz (athermal); 1 MHz; and 5 MHz (thermal). The lasing capability of Yb3+ doped lead-germanate waveguides is verified in the near-IR. The refractive index contrast (∆n) for 100 kHz WGs is ~ 1 × 10–4, while for 5 MHz, ∆n increases to ~ 5 × 10–4. The WGs in the thermal regime are less effected by self-focusing and are larger in dimensions with reduced propagation losses. For the 1 MHz repetition rate thermal writing regime we report a low propagation loss WG (0.2 dB/cm) and demonstrate laser operation with slope efficiencies of up to ~ 28%.